Development and feasibility of a Patient Blood Management implementation programme in vascular surgery. (February 2020) - Chau, Marisa; Gohil, Divisha; Schofield, Nick; Abeysiri, Sandaruwani; Klein, Andrew A; Richards, Toby
Vascular surgery is the largest (non-cardiac) user of blood transfusion which is associated with increased risk to patients. Patient Blood Management (PBM) is a quality improvement programme in transfusion medicine involving educational change and recommendations through preoperative, operative, and postoperative surgery. We wished to assess the feasibility to implement a PBM programme in vascular surgery. A multidisciplinary programme was developed at a vascular unit by PBM experts. The PBM programme involved a series of educational lectures, consultations, and discussions with doctors, nurses, and theatre staff. A one-page PBM checklist of recommendations was developed for all patients undergoing vascular surgery. Prospective audits were conducted before (October 2014 to March 2015) and after (November 2015 to February 2016) PBM implementation. Outcomes were blood transfusion and haemoglobin concentration (Hb) trigger threshold. A total of 211 patients were admitted under vascular surgery: 127 for Audit 1 and 84 for Audit 2. Overall, 30% of patients were transfused, with 193 units transfused in Audit 1 and 85 in Audit 2. PBM implementation was associated with a reduction in patients receiving a blood transfusion (37% to 20%; p = 0.01). However, there was no difference in Hb trigger threshold (76 g/L vs 72 g/L, p = 0.051). A PBM programme is feasible and can be implemented in vascular surgery. PBM was associated with an improvement in transfusion use and length of patient stay that merits further investigation.